2018
DOI: 10.18632/oncotarget.25189
|View full text |Cite
|
Sign up to set email alerts
|

Combined abiraterone acetate plus prednisone, salvage prostate bed radiotherapy and LH-RH agonists (CARLHA-GEP12) in biochemically-relapsing prostate cancer patients following prostatectomy: A phase I study of the GETUG/GEP

Abstract: BackgroundTo establish the maximum tolerated dose of abiraterone acetate plus prednisone (AA) combined with salvage radiotherapy (SRT) and goserelin in a phase 1 study in men with rising PSA following radical prostatectomy.MethodsAA was given during one month before SRT at 1000 mg PO once daily, then 750 mg (Dose Level 1, DL1) or 1000 mg (DL2) during 5 months combined with 6-months goserelin by injection on the first day of irradiation (scheme NEO) or one month before starting SRT (scheme CONCO).ResultsIn sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Thus, a further intensification of therapy may be warranted for patients with PET-positive lymph nodes or distant metastases. This might possibly be resolved by either the administration of higher radiation doses to PET-positive regions [ 39 ], an enlargement of radiation volumes [ 40 ], or by adding more aggressive systemic therapy regimens like concomitant docetaxel or abiraterone to sRT [ 41 , 42 ]. However, it is worth mentioning that patients with no metastases on PET and favorable accompanying risk factors had high two- and three-year BRFS rates of >74% and >66%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a further intensification of therapy may be warranted for patients with PET-positive lymph nodes or distant metastases. This might possibly be resolved by either the administration of higher radiation doses to PET-positive regions [ 39 ], an enlargement of radiation volumes [ 40 ], or by adding more aggressive systemic therapy regimens like concomitant docetaxel or abiraterone to sRT [ 41 , 42 ]. However, it is worth mentioning that patients with no metastases on PET and favorable accompanying risk factors had high two- and three-year BRFS rates of >74% and >66%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Three trials of abiraterone combined with rt were found (Table iv). A single phase i study investigated the safety of combining abiraterone with salvage rt 54 and two phase ii trials evaluated efficacy based on the extent of castration as assessed by testosterone level 52,53 . The two phase ii trials varied in their populations and adt durations.…”
Section: Clinical Trials Combining Abiraterone Acetate With Rtmentioning
confidence: 99%
“…[14][15][16][17] Previous studies have demonstrated the efficacy and safety of ARTAs combined with radiotherapy in high-risk patients. [18][19][20] A few studies have shown that adding palliative radiotherapy to ARTA treatment in patients with oligoprogression prolongs the disease control during ARTA treatment. 21,22 However, the role of SBRT in oligoprogressive lesions during ARTA treatment and the effect of MDT on delaying NEST have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the efficacy and safety of ARTAs combined with radiotherapy in high‐risk patients 18–20 . A few studies have shown that adding palliative radiotherapy to ARTA treatment in patients with oligoprogression prolongs the disease control during ARTA treatment 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation